The The Influence of Principal’s Leadership, Teacher Performance And Internal Quality Assurance System in Improving The Quality of Education in Vocational High School: he Quality of Education in Vocational High School - Muhammad Abdul Rahman; Achadi Budi Santosa; Hotmaulina Sihotang (Kelola: Jurnal Manajemen Pendidikan, 2020)
This study aims to determine the extent of the influence of the Principal Leadership, Teacher Performance, and the internal quality assurance system either partially or simultaneously on quality improvement at SMK Muhammadiyah 1 Bambanglipuro and SMK Negeri 1 Pandak. The study population was all teachers in the two schools, each of which was taken 35 teachers as a sample. Data collection was carried out by observation and questionnaires. Data were tested using validity, reliability, linearity, multicollinearity, and heteroscedasticity tests. Data analysis was then performed using multiple regression analysis, t-test, F test, and determination coefficient. The results show that; first, the school principal leadership, teacher performance, and internal quality assurance systems have a significant effect on improving the education quality of SMK Muhammadiyah 1 Bambanglipuro, where the contribution given is 23.40% and the regression equation obtained is Ŷ = 3,138 + 0,106X1 + 0,109X2 + 0,086X3, while the principal’s leadership, teacher performance, and internal quality assurance system together have a significant effect on improving the education quality at SMK N 1 Pandak, where the contribution is 26.50% and the regression equation obtained is Ŷ = 3,378 + 0,150X1 + 0,162X2 + 0,049X3. Second, there is a difference in quality improvement, which shows that there are significant differences in quality between SMK Muhammadiyah 1 Bambanglipuro and SMKN 1 Pandak.